Comparative estimation of the age of persons first recognized as disabled due to different eye diseases - N. M. Rustamova (Oftalʹmologiâ)
the aim of this research is to obtain comparative characteristics of the age of persons first recognized as disabled due to oph- thalmopathology. Comparison of the age composition of the disabled due to corneal diseases, the lens, retina, eyeball, optic nerve, macular degeneration, glaucoma, myopia, trauma and anophthalmos was conducted. It has been established that very early disability is characteristic of myopia, anophthalmos, eye trauma, optic atrophy and eyeball diseases. Primary disability due to diabetic retinopa- thy, uveitis and glaucoma comes much later. It is considered that the age of the patient at the moment of primary disability should beused to characterize medical and social burden of ophthalmopathology.